2021
DOI: 10.1038/s41598-021-85096-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of the matricellular protein periostin in paediatric inflammatory bowel disease

Abstract: The precise role of periostin, an extra-cellular matrix protein, in inflammatory bowel disease (IBD) is unclear. Here, we investigated periostin in paediatric IBD including its relationship with disease activity, clinical outcomes, genomic variation and expression in the colonic tissue. Plasma periostin was analysed using ELISA in 144 paediatric patients and 38 controls. Plasma levels were assessed against validated disease activity indices in IBD and clinical outcomes. An immuno-fluorescence for periostin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Periostin has been shown to be upregulated in the subepithelial region in asthma (10), AD (37,49), allergic conjunctivitis (AC) (52), eosinophilic esophagitis (EoE) (31) and familial idiopathic pulmonary fibrosis (IPF) (47,48). Periostin is also upregulated in chronic inflammations such as IBD and rheumatoid arthritis (RA) (16,28,29). Interestingly, IL-24 and STAT-3 as downstream effectors of periostin are enhancing the epithelial-barrier dysfunction thereby further fuelling the inflammatory process (92).…”
Section: Periostin In Allergy and Chronic Inflammationmentioning
confidence: 99%
See 3 more Smart Citations
“…Periostin has been shown to be upregulated in the subepithelial region in asthma (10), AD (37,49), allergic conjunctivitis (AC) (52), eosinophilic esophagitis (EoE) (31) and familial idiopathic pulmonary fibrosis (IPF) (47,48). Periostin is also upregulated in chronic inflammations such as IBD and rheumatoid arthritis (RA) (16,28,29). Interestingly, IL-24 and STAT-3 as downstream effectors of periostin are enhancing the epithelial-barrier dysfunction thereby further fuelling the inflammatory process (92).…”
Section: Periostin In Allergy and Chronic Inflammationmentioning
confidence: 99%
“…In a recent study, all expressed periostin isoforms in the small intestine were described. Interestingly, periostin variants 1, 5, 6 and 7 were detected but not the full length (see details in Figure 3) (28). Periostin has also been linked to the increased risk of colitis-associated colorectal cancer in a mouse model and its expression is also elevated in IBD patients (30).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Periostin contains an N-terminal secretory signal peptide, followed by a cysteine-rich domain (EMI domain), four FAS1 domains, and a hydrophilic carboxy-terminal domain (CTD) that shows a remarkable amount of alternative splicing ( 12 , 14 ). Recent studies have demonstrated that periostin plays a role in IBD; however, the precise mechanisms through which it influences the immune signaling pathways in IBD in patients and animal models are still not fully understood ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%